A pan-cancer analysis of synonymous mutations - Yogita Sharma; Milad Miladi; Sandeep Dukare; Karine Boulay; Maiwen Caudron-Herger; Matthias Groß; Rolf Backofen; Sven Diederichs (Nature Communications, 2019)
Synonymous mutations do not alter amino acid sequence but may exert oncogenic effects in other ways. Here, the authors present a catalogue of synonymous mutations in cancer and characterise their properties.